RETHINKING AUTHORS’ CONSENT AND PERFORMERS’ USE IN THE INDONESIAN COPYRIGHT ACT - Andrini, Laurensia (Fakultas Hukum Universitas Islam Indonesia, 2025)
Disputes between Indonesian songwriters and performers have intensified as composers become more assertive about their copyright. A dispute between a songwriter and a performer highlights the legal ambiguity between Article 9(2) of the 2014 Copyright Act that requires prior permission for any commercial use of a work, while Article 23(5) of the same Act allows performers to use work publicly once royalties are paid through a Collective Management Organization (CMO). This doctrinal study focuses on two discussions: i) the scope of an author’s right to prohibit performances of their songs; and ii) the relationship between Article 9(2) and 23(5) of the 2014 Copyright Act. This research employs a normative juridical method, relying on statutory interpretation, legal doctrine, and case-based analysis. It also includes a comparative approach by examining practices of CMOs in other jurisdictions to contextualise the Indonesian framework. This research finds that i) the right to prohibit performance is rooted in moral rights and may be invoked only to prevent harm to the author’s honour or reputation; and ii) Article 23(5) operates as a special rule that overrides Article 9(2) only to the extent of performances, provided royalties are channelled through a CMO.